2009
DOI: 10.1136/bjo.2008.155200
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of early-onset glaucoma after infant cataract extraction with and without intraocular lens implantation

Abstract: 33Aims: To determine the incidence of glaucoma, with onset within one year after the date 34 of cataract surgery (early onset) performed in the first year of life, with or without 35 intraocular lens (IOL) implantation. 36Methods: A retrospective review of a single surgeon's cohort from 1999 to 2006. 37 Glaucoma onset risk, comparison of aphakic/ pseudophakic eyes and IOL type were 38 analysed together with microcornea, persistent fetal vasculature (PFV) and age

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 27 publications
3
32
1
Order By: Relevance
“…15,31 Ken Nischal's group have recently shown that when congenital cataract surgery is traumatic the risk of glaucoma may increase. 33 In a series of 98 eyes of 62 children who had congenital cataract surgery during the first year of life, 9.8% of aphakic eyes and 13.5% of pseudophakic eyes developed glaucoma over a mean follow-up period of 2.5 years. Although there was no statistically significant effect of age on the rate of early-onset glaucoma there were four cases in which an IOLs was placed in the bag but had to be removed and all four of these eyes developed glaucoma within 14 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…15,31 Ken Nischal's group have recently shown that when congenital cataract surgery is traumatic the risk of glaucoma may increase. 33 In a series of 98 eyes of 62 children who had congenital cataract surgery during the first year of life, 9.8% of aphakic eyes and 13.5% of pseudophakic eyes developed glaucoma over a mean follow-up period of 2.5 years. Although there was no statistically significant effect of age on the rate of early-onset glaucoma there were four cases in which an IOLs was placed in the bag but had to be removed and all four of these eyes developed glaucoma within 14 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although these articles reported no increase in intraocular pressure (IOP) after surgery, postoperative ocular hypertension is a possible complication of this drug, 10 as well as of congenital cataract surgery itself. [11][12][13] The authors who have investigated the effects of triamcinolone on the corneal endothelium have suggested possible microstructural damage resulting in thicker corneas that could have an effect on the IOP measurement. [14][15][16] The purpose of the current study was to assess the IOP and central corneal thickness (CCT) in children \2 years of age who underwent congenital cataract surgery with an injection of 1.2 mg/0.03 mL of preservative-free triamcinolone acetonide into the anterior chamber at the end of the procedure to modulate postoperative inflammation.…”
Section: Resultsmentioning
confidence: 98%
“…1 Published studies have reported varied incidences of ocular hypertension secondary to triamcinolone use, ranging from 21% after sub-Tenon's injections [3][4][5] to 56% after intravitreal injections. 10,22,23 In addition to the risk of increased IOP due to triamcinolone use, pseudophakic children face a greater risk of developing ocular hypertension and glaucoma after the congenital cataract surgery itself, 11,12 which has been reported in up to 24.4% of patients. 12 There was no significant difference in the mean CCT before and after surgery in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…10 In summary, lensectomy was performed through 2 corneal incisions using automated aspiration and irrigation; this was followed by posterior capsulotomy and anterior vitrectomy. A 2-incision push-pull capsulorhexis technique was used for the anterior capsulotomy and posterior capsulotomy as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 In addition, some recent studies found that the earlier the surgical extraction of a pediatric cataract, the higher the risk for postcataract-extraction glaucoma, 7,8 independent of other factors, although other studies did not replicate this finding. 4,9,10 The use of intracameral dexamethasone has been found to significantly reduce the quantity of aqueous inflammatory cells in glaucomatous eyes and control eyes 1 day after phacoemulsification in adults while causing little risk for intraocular pressure (IOP) elevation. 11 Regarding corneal safety, dexamethasone was found to increase the sodium, K-ATPase activity, and pump function of cultured mouse corneal endothelial cells.…”
mentioning
confidence: 99%